Evolution of inland container distribution among the cluster of ports in the Greater Pearl River Delta. Issue 4 (October 2014) - Wang, Aihu; Lai, Suhong; Mohmand, Yasir Tariq
<x content-type="archive" xml:space="preserve">Abstract</x> Goal programming (GP) is applied to obtain the cargo distribution ratio from hinterland to port cluster in the absence of statistical data. Non-parametric test techniques and correlation analysis are used to analyze the stability of cargo distribution and ordinal preference in port selection. A case study for the inland container distribution in the Greater Pearl River Delta (GPRD) of China shows that most hinterland districts maintain a stable port selection pattern except for Shenzhen, in which many ports are located and which is also close to Hong Kong, another important port in the region. Although Hong Kong is important for international logistics and is one of the busiest and most efficient container ports, it does not provide great advantages for attracting cargoes from the GPRD. In the long run, the best strategy is cooperation rather than competition, which will maximize the overall benefit of the container port cluster in the GPRD.